Pinocchio - Collodi, Carlo (Italy White Star Kids, 2019)
All children can discover or rediscover their favourite characters and identify themselves in their adventures thanks to these original texts, updated in modern, accessible language, perfect for the littlest ones as well as those already able to read on their own. Enriching and completing the narratives are the colourful and captivating illustrations by Francesca Rossi, an artist who gives a fresh, modern touch to timeless classics. This is the Fairy Tale Pinocchio Story, a Bedtime Story in English for Kids. This story has been adapted from The Adventures of Pinocchio (1883) by Italian writer Carlo Collodi and the Disney version.
7+
Keywords: Adaptation